MUTUAL INTELLIGIBILITY OF MALAY- AND SWEDISH-ACCENTED ENGLISH: AN EXPERIMENTAL STUDY - Jeong, Hyeseung Jeong; Othman, Juliana; Thorén, Bosse (Universitas Pendidikan Indonesia, 2017)
In using English as an international language (EIL), one important issue is mutual intelligibility among EIL speakers from different language backgrounds. The present study investigates the cross-linguistic intelligibility of Malay-accented English and Swedish-accented English, regarding the three phonetic features – word stress pattern, consonant clusters, and long vowel in particular. We prepared 15 English statements that are evidently true or false if understood, and examined to what extent the three phonetic features are related to 30 Swedish and 38 Malaysian listeners’ understandings of the statements read by a speaker from the other language group. We compared the Malaysian and Swedish listeners’ answers given with understanding as well as processing time to respond. The listeners’ own accounts of their struggles in understanding the speakers’ pronunciations were also analyzed. Results show that Malaysian listeners easily understood Swedish-accented English, while Swedish listeners struggled to understand Malay-accented English. The difference between the two groups of listeners seems to be closely related to the degree of the realization of the three phonetic features by the speakers as well as to the degree of the use of these features as perceptual cues by the listeners. Based on the findings, we discuss potential phonetic core features of EIL for intelligibility and some pedagogical implications for teaching English pronunciation to the learners of the language.